Gerakan Teosofi dan Pengaruhnya Terhadap Kaum Priyayi Nasionalis Jawa 1912-1926 - Pradipto Niwandhono (Universitas Gadjah Mada, 2014)
This paper explores the history of the Theosophical Society in colonial Indonesia within the perspective of intellectual history and how it impact the thoughts of Javanese nationalist-aristocrat. The theosophical movement shared the same ideals with Dutch association policy. The main idea is to raise Eastern culture and society to become equals with Western civilisation. The theosophical movement had major contribution in the Javanese cultural revival movement. Many aspect of Theosophy’s teachings dealt with Indian esoteric cult, which had a strong impact to the vision of Javanese cultural nationalist: that the ideal Javanese society is no other than ancient Javanese civilisation under Hindu-Buddhist tradition.